The Influence Of Return On Equity, Debt-To-Equity Ratio, and Price To Book Value On Stock Prices (In Consumer Cyclicals Subsector Companies Listed On The Indonesia Stock Exchange For The Period 2018-2025) - Dina Monica Sirait; Salza Adzri Arismutia; Santi Damayanti; Diah Febriyanti (CV Putra Publisher, 2026)
This study examines the impact of Return on Equity (ROE), Debt to Equity Ratio (DER), and Price to Book Value (PBV) on the stock prices of Consumer Cyclical companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2025. Employing a quantitative, descriptive-verificative approach, data from 16 purposively selected companies (128 observations) were analyzed using their annual financial reports from the official IDX website. The analysis involved descriptive statistics, classical assumption tests, multiple linear regression, the coefficient of determination, and hypothesis testing. The findings indicate that ROE and PBV significantly positively influence stock prices, while DER does not. These variables collectively explain 44.4% of the variation in stock prices, highlighting the relevance of financial ratios for fundamental analysis in the Consumer Cyclicals sector.